Powszechne towarzystwa emerytalne jako organizacje sieciowe - Prudzienica-Grunt, Maja (The General Pension Societies as the Network Organizations, 2005)
The main aim of this article was to show similarities and differences between network organizations and General Pension Societies. It is obvious that the subject has not been thoroughly exhausted, it can be only the beginning of discussion. From the above analysis it follows that certain similarities are because general pension societies are sometimes members of financial groups from which they have been founded. The range of those similarities is limited to rules of the bill of pension funds' founding and functioning. The bill restricts unconstrained economic decisions making so these sociaties can not change into another forms of network organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 390-395